An exploratory international comparison of professional confidence in volunteer policing. (June 2017) - Wolf, Ross; Pepper, Ian; Dobrin, Adam
Police volunteers are an important asset to communities and policing agencies but have been relatively understudied. Similar models of police volunteers have developed in the United States and the United Kingdom but these differ in the level of their preparedness and training. This current study utilises vignettes to examine the confidence of volunteer police officers from two agencies, one in the US and one in the UK. Results show that while both groups in the study are confident in their professional ability to handle issues at a policing scene, UK volunteer officers feel less confident about interviewing and administrative paperwork than their US counterparts.